Bevacizumab radiosensitizes non-small cell lung cancer xenografts by inhibiting DNA double-strand break repair in endothelial cells. Issue 1 (28th August 2015) - Gao, Hui; Xue, Jianxin; Zhou, Lin; Lan, Jie; He, Jiazhuo; Na, Feifei; Yang, Lifei; Deng, Lei; Lu, You
Highlights Biweekly bevacizumab induces periodical vascular normalization in NSCLC xenograft model. Radiosensitization induced by bevacizumab is not dependent on vascular normalization. Bevacizumab inhibits DSBs' repair of ECs post irradiation, and promotes their apoptosis. Bevacizumab inhibits the activation of PI3K/Akt/DNA-PKcs signaling pathway post irradiation.